Applying a Resource-Based View to the Competitive Advantage of Small and Micro-Sized Firms - Petružis, Gvidas (Socialiniai tyrimai, 2018)
The object of the research is the application of resource-based view to small and micro-sized firms. The purpose of the research is to reveal the scope of the theoretical aspects of the resource-based view capabilities for small and micro-sized firms. The methods applied in the research were the analysis of the scientific literature and data and information structuring. The resource-based view (further – RBV) should help firms to discover the similarity of their competitive advantage against other companies. It is presumed that applying RBV, small and micro-sized firms can position and compete not only in a small local market in which they operate, but also could target themselves for global objectives.Limitations of the study. The recommendations of this research cannot be applied to a particular firm without undertaking these activities, the company specifics and segmentation.The concept of resource-based view and the origins of its formation. Based on Barney (1991), resource-based view is an economic tool for assessing the available strategic resources in a firm. The author formalized this theory on the basis of the idea raised by Wernerfelt (1984), that lack of resources has become an obstacle to enter the desired school. According to the author, resource-based theory is to identify the firm’s core resources and assess whether these resources are in line with the criteria for strategic resources.Developing the firm’s business strategies, four main reasons for measuring the firm’s core resources and competences (Bourne, 2016) are pointed out: 1) such measurements empower to easier plan short-term and long-term strategies; the majority of firms measure their performance by evaluating performance indicators (turnover, profit); focusing on resource development, attention is focused on the future; 2) these measurements focus on resources, that allow to improve, not the goals to be achieved; 3) the key inner factors influencing the firm’s activities are better understood and assessed; 4) if resources and competencies are not measured, the firm’s actions may be more directed to large-scale changes / measures, whilst internal resources may be left to develop without specific goals.In risky business environment, firms that are strategically driven, have greater potential for growth. In the meantime, exploration of competitors reduces the potential of growth. In addition, the firm’s manager is classified as a strategic asset of the firm with its own growth value. Entrepreneurs are those who have resources, develop operational capacities, and are looking for alternative competencies. This approach applies to businesses with business leaders. The ability of the company to develop, transfer and differentiate its intangible assets determines its long-term performance and competitive advantage.Runyan, Huddleston and Swinney (2007) studied the use of RBV for small firms. The authors conducted a quantitative study to highlight the importance of resources, creating a competitive advantage and improving performance in small businesses. The study sought to show owners of small businesses that apart nonmonetary (tangible) resources there are non-monetary, i.e. intangible resources.A research by Khan (2013) showed the interconnectedness of social capital, knowledge and entrepreneurial orientation with the use of RBV in small and very small transport companies. The results of the research emphasize the role of mediation of entrepreneurship orientation between activity knowledge and its results. Based on the RBV VRIO system (Barney, 2007), an enterprise must have an organizational capacity to strategically exploit its valuable, rare and unique strategic assets. The results indicate that entrepreneurial orientation is an example of this organizational capability that uses and exploits valuable business knowledge in the firm. The study states that knowledge becomes a strategic asset if the business has a business orientation to use this knowledge to identify and exploit business opportunities to become competitive and to benefit from positive returns.Schroeder, Bates and Junttila (2002) conducted a study to assess the potential competitiveness of the production firms, on the basis of RBV. The study found that non-educated employees working with standard equipment will not reach high productive performance. Greater productivity will reach educated employees working with specialized equipment. The study revealed the importance and necessity permanently to develop internal and external knowledge as a strategic resource. The results of the research showed that the firm must have the resources and the opportunities to use them, with a view to the company’s growth. An entrepreneur is a strategic resource, with inner growth. It can be argued that the entrepreneur firms are those that have the resources to develop the operational capacity, looking for an alternative competence.Following the analysis of the scientific literature sources and documents, it appears that small and microsized firms have limited resources. Corporate executives, aiming at long-term competitive advantage, could apply SWOT analysis, with emphasis on the development of the existing and creating necessary strategic internal resources.The results of the study showed that the firms must have the resources and the opportunities to use them, with a view to the firm’s growth. Firm manager is a strategic resource, with inner growth. It can be concluded that the entrepreneurial companies are those that have the resources to develop the operational capacity, looking for an alternative competence.The analysis has shown that small and microsized firms have to develop the competencies of an entrepreneurial executive, whose ability to develop and implement strategies for the firm’s operation is one of the main long-term competitive advantages. All of the company’s existing intangible strategic resources (entrepreneurial executive, social capital, the ability to develop and implement the company’s business strategies, operational model, knowledge and expertise, the company’s notoriety, the relationship with the customer) are mutually closely related and mutually reinforcing.To conclude, it can be stated, that owners of small and micro-sized firms have to have a clear understanding of what are tangible and intangible assets of the firm. The realization of the importance of non-monetary (intangible) resources and having competencies to strengthen existing and developing new, will create the way for a successful firm operation and development.
Keywords: esource-based view of competitive advantage; fixed; intangible and tangible resources; small and micro-sized firm